Erros ortográficos em produções escritas de alunos do 8º ano do Ensino Fundamental: uma proposta de trabalho - Stumpf, Michele Cristiane (2015)
The work with Portuguese language in the Elementary and final school grades has provoked reflections of questions related to the knowledge of writing. Among the aspects that involves the text organization, there are the paragraphs, punctuation, the use of capital and lower letters and the spelling, which, in parts, is related to the usage of language in the oral part and the reading practice, to dominate the written code. The teaching of orthography, foreseeing the relation between speaking and writing, and the crossing relations and arbitrary of language, it is a challenge for Portuguese teachers, mainly, because the students mistakes and doubts are still present in the final grades of Elementary School. The orthography has the important role to permit the reading, because it depends on the speaking, pronunciation or the reader s dialect, the writing is going to be only one. The domain of the written code helps the student to understand the language and it gives him autonomy to use writing in the several communication spheres. In the final grades of Elementary school, the orthographic registers that violate the written rules can lead the student to become a reader and text producer that has its development failed, in the formal plan and in the content plan. Among the problems found in the written productions of students (inappropriate usage of capital and lower letters, lack of punctuation, lack of accentuation, lack of cohesion and coherence, lack of verbal or nominal concordance), the most typical are the change of letters and the omission or addiction of letters. . In this research, we aim, for means of written productions from students of the 8th grade from Elementary School, to identify, describe, analyze, classify the orthographic registers and, from the occurrence of the phenomena and phonologic processes, to plan and provide reading activities, writing and linguistic analyses, turned to the orthography. Building on Oliveira (2005) studies, this research is organized from the investigation of the relation between speaking and writing and the study about the way the student uses to assimilate and domain the written language, separating it from the speaking and the system s opacity. When the student goes at school he already has his first language, and, in his speaking, he can use it efficiently in situations of interaction. Being the oral part the main communication, it is necessary to consider that from the speaking the student is introduced in the written language. In this sense, work with the written language must take as a reference the operation of speech and the reality that is considering the issues of linguistic variation present in the speech community of the student, considering that, to overcome the doubts and conflicts writing, the student begins to deepen their knowledge of the other levels of language and language.